Energy-efficient analog beamforming with short packets in millimeter-wave MIMO systems - Jordi Borràs; Francesc Molina; R. López-Valcarce; Josep Sala (2020 54th Asilomar Conference on Signals, Systems, and Computers, California, 2020, 2020)
The energy-aware design of fully analog precoders and combiners is investigated in this paper. To that aim, we consider a millimeter-wave short-packet communication scenario where power consumption and hardware complexity constitute relevant factors. User terminals employ a single channel encoder and, at hardware level, they implement analog architectures that combine phase shifters and switches. Additionally, transmitting terminals also leverage a power control system. An energy efficiency figure of merit is considered, and its optimization subject to finite packet-length constraints is tackled cyclically over disconnected feasible sets. Numerical results are reported firstly, to illustrate the advantages of the proposed short-packet fully analog design, secondly, to compare its performance to that of on-off beamforming, and finally, to discuss the optimality of the proposed optimization algorithm.
Keywords: mmWave; rodin